Video feedback and 2-dimensional landing kinematics in elite female handball players - Benjaminse, A.; Postma, W.; Janssen, I.; Otten, E. (Journal of Athletic Training, 2017)
Context: In team handball, an anterior cruciate ligament injury often occurs during landing after a jump shot. Many intervention programs try to reduce the injury rate by instructing athletes to land more safely. Video is an effective way to provide feedback, but little is known about its influence on landing technique in sport-specific situations.